Modulation of Differentiation and Bone Resorbing Activity of Human (Pre-) Osteoclasts After X-Ray Exposure - Eckert, Denise; Rapp, Felicitas; Tsedeke, Ayele Taddese; Kraft, Daniela; Wente, Isabell; Molendowska, Jessica; Basheer, Sidra; Langhans, Markus; Meckel, Tobias; Friedrich, Thomas; Donaubauer, Anna-Jasmina; Becker, Ina; et al. (Frontiers in Immunology, 2022)
Low-dose radiotherapy (LD-RT) is a local treatment option for patients with chronic degenerative and inflammatory diseases, in particular musculoskeletal diseases. Despite reported analgesic and anti-inflammatory effects, cellular and molecular mechanisms related to osteoimmunological effects are still elusive. Here we test the hypothesis that X-irradiation inhibits the differentiation of precursor osteoclasts into mature osteoclasts (mOC) and their bone resorbing activity. Circulating monocytes from healthy donors were isolated and irradiated after attachment with single or fractionated X-ray doses, comparable to an LD-RT treatment scheme. Then monocytes underwent ex vivo differentiation into OC during cultivation up to 21 days, under conditions mimicking the physiological microenvironment of OC on bone. After irradiation, apoptotic frequencies were low, but the total number of OC precursors and mOC decreased up to the end of the cultivation period. On top, we observed an impairment of terminal differentiation, i.e., a smaller fraction of mOC, reduced resorbing activity on bone, and release of collagen fragments. We further analyzed the effect of X-irradiation on multinucleation, resulting from the fusion of precursor OC, which occurs late during OC differentiation. At 21 days after exposure, the observation of smaller cellular areas and a reduced number of nuclei per mOC suggest an impaired fusion of OC precursors to form mOC. Before, at 14 days, the nuclear translocation of Nuclear Factor Of Activated T Cells 1 (NFATc1), a master regulator of osteoclast differentiation and fusion, was decreased. In first results, obtained in the frame of a longitudinal LD-RT study, we previously reported a pain-relieving effect in patients. However, in a subgroup of patients suffering from Calcaneodynia or Achillodynia, we did not observe a consistent decrease of established blood markers for resorption and formation of bone, or modified T cell subtypes involved in regulating these processes. To assess the relevance of changes in bone metabolism for other diseases treated with LD-RT will be subject of further studies. Taken together, we observed that in vitro X-irradiation of monocytes results in an inhibition of the differentiation into bone-resorbing OC and a concomitant reduction of resorbing activity. The detected reduced NFATc1 signaling could be one underlying mechanism.